2015
DOI: 10.1111/dmcn.12762
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive seating systems in children with severe cerebral palsy across International Classification of Functioning, Disability and Health for Children and Youth version domains: a systematic review

Abstract: AIM The aim of this study was to systematically review the effect of adaptive seating systems (AdSSs) in young people less than 19 years of age with severe cerebral palsy (CP), with particular focus on child-related outcomes across all components of the functioning and disability domains of the International Classification of Functioning, Disability, and Health for Children and Youth version (ICF-CY).METHOD Literature searches of studies published from 1975 to October 2014 were performed.Methodological quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 49 publications
(417 reference statements)
1
28
0
2
Order By: Relevance
“…10,18,26 The results of this study showed that there is a very obvious need for postural support for seating in children with CP, since there was a significant difference in most In the present study, GMFCS Level 3, 4, and 5 children were included because the children in these levels require seating systems more, and it has been reported numerous times that as the level increases, their need for seating systems also increases. 11,17 It was surprising (because it contradicts with the literature) to see that there were differences among groups in terms of all SPCM values in both all children ungrouped as well as grouped, and paired comparisons showed no difference between seating groups except in Level 4 children. An analysis of these results showed that the differences in most items of SPCM were between SC and the other applications, and AdSS and CMO yielded similar results.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…10,18,26 The results of this study showed that there is a very obvious need for postural support for seating in children with CP, since there was a significant difference in most In the present study, GMFCS Level 3, 4, and 5 children were included because the children in these levels require seating systems more, and it has been reported numerous times that as the level increases, their need for seating systems also increases. 11,17 It was surprising (because it contradicts with the literature) to see that there were differences among groups in terms of all SPCM values in both all children ungrouped as well as grouped, and paired comparisons showed no difference between seating groups except in Level 4 children. An analysis of these results showed that the differences in most items of SPCM were between SC and the other applications, and AdSS and CMO yielded similar results.…”
Section: Discussionmentioning
confidence: 81%
“…5,7,23,24 Adaptive seating systems for the treatment of children with CP have been utilized for the improvement of positioning and functioning and for the prevention of various secondary complications. 11 With additional accessories, adaptive seating equipment is used to activate functionality. Researchers have been working to improve limited postural control, functional potential, and poor sitting balance using appropriate sitting positions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In non-ambulatory patients, methods of optimizing seating position have been shown to provide increased support and improve functional outcomes (23). Few studies have focused on the effect of seating systems on correction of spinal deformity.…”
Section: Non-surgical Managementmentioning
confidence: 99%